Trajetória política e intelectual de Clóvis Moura (1959- 1989): quilombagem, práxis negra e antirracismo de um intéprete do Brasil - Silva, Wanessa Horrana Francisca da (2021)
ABSTRACT: This dissertation consists of a research on the political and intellectual trajectory of Clóvis Steiger de Assis Moura (1925-2003) in order to understand the path taken by him from his childhood to the publication of the emblematic Slavery Rebellions (1959) and to understand how he constructed his interpretation of the history of Brazil, placing the enslaved as an active agent in this process. In the research, we chose to verify the social and political articulations, their circulation in newspapers, magazines and analyze the foundation and articulation process of the Brazilian Institute of Africanist Studies (IBEA) as we understand that the trajectory of the IBEA is traversed by the historical and political experience of its founder Clovis Moura. In this way, I seek to understand how the institute's founding process took place, its articulation and exchange with various national and international entities that studied African history, the research carried out and developed, lectures, practices and contributions from intellectuals linked to the IBEA. To investigate these relationships is to understand how these commitments helped him to build his thesis on active and political blacks in the emancipation process. For a better approach to these issues, we chose to analyze his historical and sociological production that brings his interpretation of Black Praxis and Quilombagem, and how the legacy of these struggles helps us to build an anti-racist society. Therefore, we chose a time frame from 1959, the year of the publication of his first book Slavery Rebellions, until 1989 with History of the Brazilian Black. Regarding the sources, we chose to analyze their bibliographic production during the proposed period and documents from the Clóvis Moura collection that is at CEDEM, which contains interviews, articles, photos, letters and documents provided by his family.